Tintenfass und Teleskop: Galileo Galilei im Schnittpunkt wissenschaftlicher, literarischer und visueller Kulturen im 17. Jahrhundert - Albrecht, Andrea; Cordibella, Giovanna; Remmert, Volker R. (Spectrum Literaturwissenschaft, 2014)
This volume explores the image of Galileo Galilei’s as a scientist of the early modern age along with cultural perceptions of his discoveries and writings. It examines the interconnections between scientific theories and practices and their textual and visual representations.